Structured Products and a Framework for Regulation - Gecer, Tuba (2006)
The term 'structured products' which refers to a broad category of hybrid financial instruments linked to the performance of an underlying asset has been the most commonly used term of the financial markets in the last two decades. While banks worldwide are enthusiastically selling structured products to increase their profitability, investors are attracted to these products in search for yield during periods of low interest rates. Although structured products are being imposed on investors by the Wall Street as a magic solution, they are subject to the same laws of risk and return as the rest of the capital market: It is impossible to increase income without incurring additional risks and it is impossible to avoid losses without accepting limitations on earnings. For that reason investors need to understand the risks. However, especially for retail investors the complexity in the design of these products makes it difficult to understand the nature of the product they are buying or to assess the risks they are taking on. Therefore regulators, whose first mission is market and investor protection, need to step in to ensure that retail investors receive fair and adequate information about their investment and are not misled into buying structured products which are not suitable for their investment needs. This study, tries to provide a comprehensive research on structured products and attempts to develop a framework to regulate structured products in order to provide an adequate level of investor protection. The framework is prescriptive in nature because it aims to regulate structured products especially in developing countries where investors are less sophisticated. It consists of product approval, defining the boundaries of regulation, providing public information, disclosures, internal control mechanisms and regulatory controls. However, the study concludes that no regulation can take the place of a protection offered by markets and market participants. Market participants should comprehend the importance of investor protection and design their activities around that understanding. As for regulators, rather than banning investors from investing into structured products, they should educate investors not to invest their money in schemes that mislead them into risky, inappropriate investments. For this reason, regulators of financial markets should strive to educate retail investors about the features and risks of structured product in order to provide a comprehensive investor protection.